Development and Characterization of a Nint-Loaded Nanoparticulate Matrix Tablet for Enhanced Solubility and Sustained Release - L.Narwade, Vaibhav; Thakare, Mahesh; Parekh, Pranav; Pavale, Mamta; Londhe, Minakshi; Chivte, Dhanshree; Punde, Priyanka; Waghmode, Pritam Suresh (Journal of Neonatal Surgery, 2025)
Nintedanib, a tyrosine kinase inhibitor, is a critical treatment for idiopathic pulmonary fibrosis but suffers from poor aqueous solubility and low oral bioavailability of approximately 4.7% due to extensive first-pass metabolism. These limitations hinder its therapeutic efficacy and necessitate frequent dosing. To overcome these challenges, a novel nanoparticulate matrix tablet was developed. Nintedanib-loaded nanoparticles were formulated using the polymer PLGA via a solvent evaporation technique and were subsequently compressed into matrix tablets by direct compression using polymers like HPMC K4M and Microcrystalline Cellulose. The prepared nanoparticles were characterized for entrapment efficiency, morphology (SEM), and physical state (XRD). The matrix tablets underwent evaluation for pre- and post-compression parameters, I understand you'd like a downloadable Word file. However, as an AI, I cannot generate files for download